A novel parameter identification approach for buffer elements involving complex coupled thermo-hydro-mechanical analyses. (June 2016) - Nguyen-Tuan, Long; Lahmer, Tom; Datcheva, Maria; Stoimenova, Eugenia; Schanz, Tom
Abstract: Coupled thermo-hydro-mechanical (THM) analyses contain a large set of constitutive parameters and this requires numerous experiments to determine these parameters. This study contributes to the identification of parameters of a coupled THM constitutive model via back analysis of information-rich experiments. An iterative sampling based back analysis approach is proposed comprising both the model parameter identification and the assessment of the reliability of identified model parameters. The results obtained in the context of buffer elements indicate that sensitive parameter estimates generally follow the normal distribution. According to the sensitivity of the parameters and the probability distribution of the samples we can provide confidence intervals for the estimated parameters and thus allow a qualitative estimation on the identified parameters which are in future work used as inputs for computational predictions in high-risk situations.